Respuesta :

9514 1404 393

Answer:

  3)  (x, y) = (-2, 8)

  5)  (x, y) = (-3, -7)

Step-by-step explanation:

3) The expression for y can be substituted into the other equation.

  4x +16 = 3x +14

  x = -2 . . . . . . . . . . subtract 3x+16 from both sides

  y = 3(-2) +14 = -6 +14 = 8

The solution is (x, y) = (-2, 8).

__

5) Substitute for y in the first equation.

  -x +2(4x +5) = -11

  -x +8x +10 = -11

  7x = -21 . . . . . . . . . subtract 10

  x = -3 . . . . . . . . . . . divide by 7

  y = 4(-3) +5 = -12 +5 = -7

The solution is (x, y) = (-3, -7).

Step-by-step explanation:

______________

3).

y = 4x + 16

y = 3x + 14

y = y

4x + 16 = 3x + 14

4x - 3x = 14 - 16

x = -2

y = 4x + 16

y = 4(-2) + 16

y = -8 + 16

y = 8

(x, y) = (-2, 8)

______________

5).

-x + 2y = -11

y = 4x + 5

-x + 2y = -11

-x + 2(4x + 5) = -11

-x + 8x + 10 = -11

7x = - 11 - 10

7x = -21

x = -3

y = 4x + 5

y = 4(-3) + 5

y = -12 + 5

y = -7

(x, y) = (-3, -7)

______________